B-type natriuretic peptides for the prediction of cardiovascular events and mortality in patients living with HIV: Results from the HIV-HEART study. (15th April 2019) - Reinsch, Nico; Streeck, Hendrik; Holzendorf, Volker; Schulze, Christina; Neumann, Till; Brockmeyer, Norbert H.; Kehrmann, Jan; Schadendorf, Dirk; Esser, Stefan
Abstract: Aims: B-type natriuretic peptide (BNP) has been suggested to improve risk prediction of cardiovascular (CV) events and mortality. We aimed to evaluate the value of BNP to predict the composite primary endpoint of CV events and mortality alongside traditional and HIV specific risk factors in a HIV-infected population. Methods: In this prospective multicenter HIV-HEART study we followed 808 HIV-positive subjects in the German Ruhr area for a median follow up of 120 (IQR:113–129) months since 2004. Association of BNP with the composite primary endpoint was assessed using Cox regression adjusting for traditional cardiovascular and HIV specific risk factors. Results: At baseline, median BNP was 10.3 (IQR 5.4–18.9) pg/ml. The composite endpoint occurred in 158 (19.6%) patients. Subjects with high BNP levels showed significantly increased frequencies of CV events and death (22% for BNP ≤5 pg/ml, 30% for BNP >5 up to ≤20 pg ml, 38% for BNP >20 up to ≤35 pg ml, 59% for BNP >35 up to ≤100 pg ml and 86% for BNP >100 pg/ml, p-value < 0.01). In the fully adjusted model that included traditional CV risks as well as HIV specific factors, after a log2 transformation, doubling of BNP was significantly associated with increased risk for the composite endpoint (HR:1.16 (95%CI 1.01–1.33); p = 0.031). Comparing BNP of <5 pg/ml to BNP > 100 pg/ml, HR in the fully adjusted model was 3.25 (95%CI 1.50–7.08; p < 0.001). Conclusions: Increased BNP is associated with significant excess of incident CV events and mortality in HIV-infected patients. BNP is a valuable marker to improve the prediction of CV events and mortality. Highlights: Elevated levels of BNP are associated with significant excess of incident cardiovascular events and mortality in HIV-infected patients. BNP improves the prediction of CVE and mortality in HIV-infected patients in addition to traditional risk factors and HIV specific parameters. Elevated BNP in HIV-infected patients may be a useful marker for risk stratification of CVD to intensify risk management and to predict mortality.